The Effect of Psychological Training on Strengthening Family Behavioral Empowerment: A Path Analysis Approach - Chotratanakamol, Krisana; Uansa-ard , Suwaluck; Longthong , Nathawat; Yaemyuean , Anan (Thammasat Review, 2024)
Preventing violence and strengthening family institutions require the enhancement of Family Behavioral Empowerment (FBE). Therefore, an experiment was conducted to provide psychological training, focusing on both psychological and skill development, aimed at improving FBE among Thai youths. This research investigated the effects of psychological training modules, characteristics, and situational factors on FBE. A total of 320 undergraduates from four Thai universities completed the training. Hypotheses based on the Interactionism Model were tested using structural equation modeling (SEM). The results indicated good fit indices for the path model (χ2 = 135.714; df = 111; p-value = 0.05; RMSEA = 0.02; CFI = 0.99; TLI = 0.99; SRMR = 0.06). Psychological training modules had a significantly direct effect on psychological states (TE = 0.49) and both direct and indirect effects on FBE (TE = 0.51). The training's effectiveness played an essential role in achieving favorable states and enhancing FBE. Psychological states exhibited the highest total effect on FBE (TE = 0.81), emphasizing the importance of fostering favorable psychological states. Psychological traits and situational factors were pivotal in shaping psychological states and indirectly contributing to FBE. These findings indicate the utility of training modules that integrate psychological and skills development, fostering positive attitudes and motivation for achievement towards FBE. Such interventions are crucial for strengthening family institutions and alleviating societal violence.